Resepsi Masyarakat terhadap Makna Simbol Nilai Kearifan Lokal Tradisi Dikili Kecamatan Patilanggio - Pou, Liska D.; Malabar, Sayama; Bagtayan, Zilfa Achmad (Ideas Publishing, 2024)
The researcher’s search in the field is expected that the listeners and chanters of dzikir appreciate the contents of Dikili that are chanted. But in reality, many people let the dzikir singers because they do not understand what the value and meaning contained in Dikili, therefore. The study seeks to depict the community’s perception of local wisdom value symbols in the Dikili tradition of Patilanggio. District utilizing qualitative and quantitative methodologies. The sources of data are the Dikili singers and respondents. The study revealed a nearly equal distribution of community acceptance towards the significance of the symbol of local wisdom’s value in the Dikili tradition of Patilanggio subdistrict with 54,59% agreeing and 45,41% disagreeing, the influential factors that affected the community’s acceptance of the meaning and value of local wisdom in the mentioned tradition were their level of knowledge and age. The study’s findings indicate that the residents of Patilanggio subdistrict mostly concur regarding the symbolism and local wisdom values